THE INFLUENCE OF PRINCIPAL ACADEMIC SUPERVISION AND TEACHER SELF-DEVELOPMENT ON THE PROFESSIONAL COMPETENCE OF STATE ELEMENTARY SCHOOL TEACHERS IN RUPAT UTARA DISTRICT, BENGKALIS DISTRICT - Dumaria Dumaria; Gimin Gimin; Sumarno Sumarno (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Principal's academic supervision and teacher self-development are top priorities in efforts to improve teacher professional competence. This study aims to determine the effect of academic supervision (X1) and teacher self-development (X2) on the professional competence of teachers (Y) in SDN throughout the district of North Rupat. This study uses a type of quantitative research. This research uses descriptive research type, with a total sample of 88 people. Simultaneously (combined) there is the effect of Principal Academic Supervision (X1) and Teacher Self-Development (X2) on Teacher Professional Competence (Y) in SDN in North Rupat District. This can be proven by t arithmetic > t table X1 of 1.735 > 1.662 and for X2 12.643 > 1.662 and a significance level (sig.) of 0.012 and 0.167, both of which are greater than 0.05, then H0 is rejected and H1 is accepted. That the percentage of the influence of the two independent variables affects the Teacher Professional Competence variable by 80.4% and the remaining 19.6% is influenced by other variables or factors that cannot be mentioned in this study.